The American University in Bulgaria: Institution-building in a Developing Democracy - Laverty, Edward; Laverty, Roberta (Maine Policy Review, 1993)
Edward and Roberta Laverty describe the new American University in Bulgaria (AUBG) that opened in September 1991. This is the first private educational institution opened in Bulgaria since World War II, and because of its affiliation with the University of Maine, it becasme the only fully accredited university in Eastern Europe..